Revisitando a sustentabilidade do endividamento público no Brasil - Mário Jorge Cardoso de Mendonça; Tito Belchior Silva Moreira; Luis Alberto Toscano Medrano; Joaquim Ramalho de Albuquerque (Instituto de Pesquisa Econômica Aplicada (IPEA), 2016)
– This study aims to examine the sustainability of the Brazilian public indebtedness using different approaches. Based on the analysis of the conditioning factors of net debt of the public sector (DLSP) in the period 2002-2014, there seems to be a change in fiscal regime between 2011 and 2014 compared to the previous period from 2002 to 2010. We propose to include Petrobras, Eletrobras and the remains payable into the DLSP. The result indicates that the difference between net debt and gross displays a sensible reduction. We apply three different cointegration tests in the series of government revenue and expenditure in order to check the sustainability of public debt. The results show no empirical evidence that public debt is long-term solvent. Finally, based on the dynamic factor model one forecasts the revenues and expenditures of the central government for 36 months ahead. It was found that the primary outcome may suffer serious deterioration since from September 2015 to August 2018 the values predicted shows a decrease in revenues while the trend for expenses is growing. This implies a further limiting factor to the sustainability and solvency of public debt.
Keywords: H24; N46; E62; 330; net indebtedness; cointegration; sustainability; dynamics factorial model; forecasting